A CoO@NC composite material and its preparation method and application
By stripping the ZIF-67 material with NaBH4 layering treatment and calcination, CoO@NC nanoparticles with high specific surface area and pore volume were prepared, which solved the problem of cumbersome preparation process and poor catalytic effect of existing MOF catalysts, and achieved rapid and efficient antibiotics Degradation effect.
Patent Information
- Application Number
- CN202211537234.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-02
AI Technical Summary
In the prior art, the preparation process of constructing porous metal organic frame material (MOF) catalysts is cumbersome, requires high temperature calcination, and the catalytic effect is poor, making it difficult to effectively degrade residual antibiotics in the environment.
After the NaBH4 layering treatment, ZIF-67 material was calcined to prepare CoO@NC composite material with a large specific surface area and rich pore volume. The ZIF-67 with a specific morphology was generated by reaction with NaBH4 under ultrasonic conditions, and then at a lower level. Calcined at temperature to obtain CoO@NC nanoparticles with good dispersion and improve the catalytic effect.
The high specific surface area and pore volume of CoO@NC nanoparticles were synthesized at lower temperatures. The rich pore structure and good dispersion improved the catalytic effect and could quickly and effectively degrade antibiotics, especially in the degradation of ofloxacin. During the test, 78% of the reaction was removed in one minute, and the removal efficiency reached 92.9% after ten minutes.
Smart Images

Figure HDA0003978226210000011 
Figure HDA0003978226210000012 
Figure HDA0003978226210000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano alloy catalysts, and in particular relates to a CoO@NC composite material and a preparation method and application thereof. Background Art
[0002] With the development of medicine, antibiotics and other drugs have been widely used in animal and plant breeding, human-related disease treatment, etc. and have achieved good results. However, incomplete absorption of antibiotics, drug abuse, and unreasonable discharge of related sewage will lead to excessive residues of antibiotics in the environment and organisms, which is one of the current threats to the health of organisms. More seriously, the residues of antibiotics will lead to the production of drug-resistant bacteria, which will increase the difficulty of future disease treatment. Therefore, controlling the discharge of antibiotics and eliminating residual antibiotics in the environment is of great significance to the health and sustainable development of the ecological environment and organisms. At present, our country has included discarded drugs and their packaging in the scope of hazardous waste to reduce the discharge of drugs into the environment. In addition, the research and development of technology for removing residual antibiotics in the environment is a current research hotspot. Due to its advantages of high degradation efficiency and rapidity, the new oxidation technology based on persulfate has received widespread attention and has made certain progress. The development of fast, stable and high-performance catalysts is the current goal that is constantly pursued.
[0003] Due to their rich and controllable structures, pore sizes and properties, high-dimensional porous materials metal organic frameworks (MOFs) are often used as precursors to construct porous composite materials of derived metals and carbon through calcination. These materials have shown good performance in the field of catalysis. Improving the porosity of calcined derived materials and the dispersibility of metal nanoparticles is the current research focus. In the prior art, MOF composite materials (such as MOF-polymers, MOF confined space-supported nanoparticles) are often constructed as precursors and calcined to obtain composite materials for catalytic materials. This type of method has the disadvantages of cumbersome preparation process, fine control, and high calcination temperature (950°C). Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the first aspect of the present invention provides a method for preparing a CoO@NC composite material, using a specific wrinkled ZIF-67 sheet material obtained after NaBH4 exfoliation as a precursor, and calcining the material to conveniently and quickly synthesize CoO@NC nanoparticles with a high specific surface area and good dispersibility, so as to achieve rapid and efficient catalytic degradation of antibiotics.
[0005] The second aspect of the present invention provides a CoO@NC composite material obtained by the preparation method of the CoO@NC composite material.
[0006] The third aspect of the present invention proposes an application of the CoO@NC composite material.
[0007] According to a first aspect of the present invention, a method for preparing a CoO@NC composite material is provided, comprising the following steps:
[0008] S1: adding NaBH4 solid to the flaky ZIF-67 under ultrasonic conditions and continuing the ultrasonic reaction to obtain the exfoliated ZIF-67;
[0009] S2: Under an inert atmosphere, the exfoliated ZIF-67 was calcined to obtain the CoO@NC composite material.
[0010] In the present invention, the flaky ZIF-67 is directly treated with NaBH4 solid to obtain ZIF-67 with specific exfoliation and surface wrinkled stacking morphology, and then calcined to obtain a composite material with large specific surface area and pore volume and good particle dispersion. Among them, the rich pore structure is conducive to the enrichment of the catalytic substrate and material transmission, and improves the catalytic effect; the well-dispersed catalytic sites are conducive to maximizing the utilization of the catalytic active center to activate the oxidant to produce active fragments (free radicals and non-free radicals).
[0011] In some embodiments of the present invention, in S1, the mass ratio of the flaky ZIF-67 to the NaBH4 solid is 1:(0.2-0.6).
[0012] In some preferred embodiments of the present invention, in S1, the ultrasonic reaction time is 2 h to 10 h.
[0013] In some more preferred embodiments of the present invention, in S1, the surface of the exfoliated ZIF-67 is wrinkled.
[0014] In some more preferred embodiments of the present invention, in S2, the calcination temperature is 400°C to 650°C, and the time is 2h to 10h; preferably, the calcination heating rate is 0.5°C / min to 2°C / min.
[0015] In some more preferred embodiments of the present invention, in S1, the method for preparing the flaky ZIF-67 comprises the following steps: adding 2-methylimidazole solution to the Co(NO3)2·6H2O solution with stirring, and continuing to stir the reaction to obtain the flaky ZIF-67.
[0016] In some more preferred embodiments of the present invention, the concentration ratio of the Co(NO3)2·6H2O solution to the 2-methylimidazole solution is 1:(1-4).
[0017] In some more preferred embodiments of the present invention, the 2-methylimidazole solution is added dropwise; preferably, the 2-methylimidazole solution is added dropwise within 10 min to 1 h.
[0018] In some more preferred embodiments of the present invention, the Co(NO3)2·6H2O solution includes any one of Co(NO3)2·6H2O aqueous solution, Co(NO3)2·6H2O methanol solution, and Co(NO3)2·6H2O water-methanol mixed solution; correspondingly, the 2-methylimidazole solution includes any one of 2-methylimidazole aqueous solution, 2-methylimidazole methanol solution, and 2-methylimidazole water-methanol mixed solution.
[0019] In some more preferred embodiments of the present invention, the stirring reaction time is 6 h to 24 h.
[0020] In some more preferred embodiments of the present invention, the method for preparing the CoO@NC composite material further comprises the step of purifying the ultrasonic reaction product in S1 or the calcined product in S2, wherein the purification comprises washing, filtering and drying.
[0021] According to a second aspect of the present invention, a CoO@NC composite material prepared by the preparation method of the CoO@NC composite material is provided.
[0022] In some embodiments of the present invention, the CoO@NC composite material is formed by calcining exfoliated ZIF-67 with wrinkled surface.
[0023] In some preferred embodiments of the present invention, the CoO@NC composite material is a porous bulk material with a particle size of 10 nm to 50 nm.
[0024] According to the third aspect of the present invention, a use of the CoO@NC composite material in catalytic degradation of antibiotics is proposed.
[0025] The beneficial effects of the present invention are:
[0026] Different from directly calcining MOF materials to construct CoO@NC, the present invention uses NaBH4 solid to pretreat ZIF-67 to achieve the construction of a precursor with a specific morphology. The resulting derivative material has a large specific surface area and pore volume at a relatively low calcination temperature (as low as 400°C), dispersed nanoparticles, and a rich pore structure that is conducive to the enrichment of catalytic substrates and material transport, thereby improving the catalytic effect; well-dispersed catalytic sites are conducive to maximizing the utilization of catalytic active centers. Compared with composite materials constructed by other means, the CoO@NC material constructed by the present invention has a wide range of synthesis conditions, convenient and fast synthesis, and can effectively activate peroxymonosulfate in the ofloxacin degradation test, removing 78% of ofloxacin in one minute of reaction, and the removal efficiency reaches 92.9% after ten minutes of reaction. The concentration of dissolved Co ions in the solution after the reaction is 0.10ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0028] Figure 1 1 is the XRD diagram of the CoO@NC composite material prepared in Example 1 of the present invention and the comparative example.
[0029] Figure 2 This is the SEM image of the flaky ZIF-67 product S1 in Example 1 of the present invention.
[0030] Figure 3 This is the SEM image of the exfoliated ZIF-67 of the S2 product in Example 1 of the present invention.
[0031] Figure 4 This is a SEM image of the CoO@NC composite material prepared in Example 1 of the present invention.
[0032] Figure 5 This is a SEM image of the CoO@NC composite material prepared in Comparative Example 1 of the present invention.
[0033] Figure 6 This is a SEM image of ZIF-67 piled up in the S2 product in Comparative Example 2 of the present invention.
[0034] Figure 7 This is a TEM image of the CoO@NC composite material prepared in Example 1 of the present invention.
[0035] Figure 8 This is a TEM image of the CoO@NC composite material prepared in Comparative Example 1 of the present invention.
[0036] Fig. 9 This is a N2 adsorption-desorption curve diagram of the flaky ZIF-67, the S1 product in Example 1 of the present invention, and the exfoliated ZIF-67, the S2 product in Example 1 at 77K.
[0037] Fig.10 The N2 adsorption-desorption curves of the CoO@NC composite material prepared in Example 1 of the present invention and the CoO@NC composite material prepared in Comparative Example 1 at 77K.
[0038] Fig.11 The pore size distribution diagram of the CoO@NC composite material prepared in Example 1 of the present invention and the CoO@NC composite material prepared in Comparative Example 1.
[0039] Fig.12 The diagram shows the effect of the CoO@NC composite material prepared in Example 1, the CoO@NC composite material prepared in Comparative Example 1, and the degradation of ofloxacin antibiotics. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0041] Example 1
[0042] This example prepares a CoO@NC composite material, and the specific process is as follows:
[0043] S1: Preparation of ZIF-67: 1.16 g Co(NO3)2·6H2O and 1.312 g 2-methylimidazole were dissolved in 200 mL water, respectively, and ultrasonicated and stirred until completely dissolved to obtain aqueous solutions of Co(NO3)2·6H2O and 2-methylimidazole. The aqueous solution of Co(NO3)2·6H2O was stirred continuously, and the aqueous solution of 2-methylimidazole was slowly added thereto (completely added within half an hour), and stirring was continued for 24 hours after complete addition, and the product was washed three times with deionized water, filtered and dried.
[0044] S2: ZIF-67 pretreatment: 2 g of ZIF-67 prepared in S1 was added to 200 mL of aqueous solution and ultrasonically dispersed evenly. 1.0 g of NaBH4 solid was quickly added under ultrasonic conditions. The ultrasonic treatment was continued for half an hour and stirred for 10 hours. The obtained product was exfoliated ZIF-67. The sample was washed three times with deionized water and filtered and dried.
[0045] S3: Preparation of derivative materials: 1 g of treated ZIF-67 was placed in a corundum crucible, put into a tubular furnace, and heated to 450°C at 2°C / min in a N2 atmosphere and calcined for 6 hours. The heating was then turned off and the furnace was cooled. The calcined sample was washed with hot water, filtered, and dried to obtain a derived CoO@NC composite material.
[0046] Example 2
[0047] This embodiment prepares a CoO@NC composite material. Compared with embodiment 1, the main difference is that when preparing the precursor, the amount of NaBH4 added is reduced to 0.4 g. The specific process is as follows:
[0048] S1: Preparation of ZIF-67: Dissolve 1.16 g Co(NO3)2·6H2O and 1.312 g 2-methylimidazole in 200 mL water, respectively, and stir and sonicate until completely dissolved to obtain aqueous solutions of Co(NO3)2·6H2O and 2-methylimidazole. Continue to stir the aqueous solution of Co(NO3)2·6H2O, slowly add the aqueous solution of 2-methylimidazole (add within half an hour), continue stirring for 24 hours after complete addition, wash the product three times with deionized water, and filter and dry;
[0049] S2: ZIF-67 pretreatment: 2 g of ZIF-67 prepared in S1 was added to 200 mL of aqueous solution for uniform ultrasonic dispersion, and 0.4 g of NaBH4 solid was quickly added under ultrasonic conditions. The ultrasonic treatment was continued for half an hour and stirred for 10 hours. The obtained product was exfoliated ZIF-67. The sample was washed three times with deionized water and filtered and dried.
[0050] S3: Preparation of derivative materials: 1 g of treated ZIF-67 was placed in a corundum crucible, put into a tubular furnace, and heated to 450°C at 2°C / min in a N2 atmosphere and calcined for 6 hours. The heating was then turned off and the furnace was cooled. The calcined sample was washed with hot water, filtered, and dried to obtain a derived CoO@NC composite material.
[0051] Example 3
[0052] This example prepares a CoO@NC composite material. Compared with Example 1, the difference is that the calcination temperature is increased to 600°C. The specific process is as follows:
[0053] S1: Preparation of ZIF-67: 1.16 g Co(NO3)2·6H2O and 1.312 g 2-methylimidazole were dissolved in 200 mL water, respectively, and ultrasonicated and stirred until completely dissolved to obtain aqueous solutions of Co(NO3)2·6H2O and 2-methylimidazole. The aqueous solution of Co(NO3)2·6H2O was stirred continuously, and the aqueous solution of 2-methylimidazole was slowly added thereto (completely added within half an hour), and stirring was continued for 24 hours after complete addition, and the product was washed three times with deionized water, filtered and dried.
[0054] S2: ZIF-67 pretreatment: 2 g of ZIF-67 prepared in S1 was added to 200 mL of aqueous solution and ultrasonically dispersed evenly. 1.0 g of NaBH4 solid was quickly added under ultrasonic conditions. The ultrasonic treatment was continued for half an hour and stirred for 10 hours. The obtained product was exfoliated ZIF-67. The sample was washed three times with deionized water and filtered and dried.
[0055] S3: Preparation of derivative materials: 1 g of treated ZIF-67 was placed in a corundum crucible, put into a tubular furnace, and heated to 600 °C at 2 °C / min in a N2 atmosphere for 6 hours, then the heating was turned off and the furnace was cooled; the calcined sample was washed with hot water, filtered, and dried to obtain a derived CoO@NC composite material.
[0056] Comparative Example 1
[0057] This comparative example prepares a CoO@NC composite material. Compared with Example 1, the difference is that untreated ZIF-67 is used as a precursor to calcine to obtain the CoO@NC sample. The specific process is as follows:
[0058] S1: Preparation of ZIF-67: Dissolve 1.16 g Co(NO3)2·6H2O and 1.312 g 2-methylimidazole in 200 mL water, respectively, and stir and sonicate until completely dissolved to obtain aqueous solutions of Co(NO3)2·6H2O and 2-methylimidazole. Continue to stir the aqueous solution of Co(NO3)2·6H2O, slowly add the aqueous solution of 2-methylimidazole (add within half an hour), continue stirring for 24 hours after complete addition, wash the product three times with deionized water, and filter and dry;
[0059] S2: Preparation of derivative materials: 1 g of treated ZIF-67 was placed in a corundum crucible, put into a tubular furnace, and heated to 450°C at 2°C / min in a N2 atmosphere and calcined for 6 hours. The heating was then turned off and the furnace was cooled. The calcined sample was washed with hot water, filtered, and dried to obtain a derived CoO@NC composite material.
[0060] Comparative Example 2
[0061] This comparative example prepares a composite material, which is different from Example 1 in that the NaBH4 aqueous solution is slowly added, and the specific process is as follows:
[0062] S1: Preparation of ZIF-67: 1.16 g Co(NO3)2·6H2O and 1.312 g 2-methylimidazole were dissolved in 200 mL water, respectively, and ultrasonicated and stirred until completely dissolved to obtain aqueous solutions of Co(NO3)2·6H2O and 2-methylimidazole. The aqueous solution of Co(NO3)2·6H2O was stirred continuously, and the aqueous solution of 2-methylimidazole was slowly added thereto (completely added within half an hour), and stirring was continued for 24 hours after complete addition, and the product was washed three times with deionized water, filtered and dried.
[0063] S2: ZIF-67 pretreatment: 2 g of ZIF-67 prepared in S1 was added to 200 mL of aqueous solution and ultrasonically dispersed evenly. Under ultrasonic conditions, NaBH4 aqueous solution (100 mL containing 0.5 g NaBH4) was slowly added dropwise within half an hour and stirring was continued for 10 hours. The obtained product was broken and peeled ZIF-67 flaky material. The sample was washed three times with deionized water and filtered and dried.
[0064] S3: Preparation of composite materials: Place 1 g of treated ZIF-67 in a corundum crucible, put it into a tubular furnace, and heat it to 600°C at 2°C / min in a N2 atmosphere and calcine it for 6 hours. Then turn off the heating and cool it with the furnace. Wash the calcined sample with hot water, filter and dry it to obtain a composite material.
[0065] Test Example 1
[0066] In this test example, the precursor in the preparation process of the CoO@NC composite material, the CoO@NC composite material obtained in Example 1 and Comparative Example 1 were subjected to XRD, SEM, TEM, N2 adsorption-desorption at 77K, and pore size distribution tests.
[0067] Figure 1 The XRD patterns of the CoO@NC composite materials prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the CoO@NC composite material prepared in Example 1 has diffraction peaks at 36.5°, 42.4° and 61.5°, and the peak of the CoO@NC composite material prepared in Comparative Example 1 at 36.5° is very weak and almost unobservable. The peaks of the samples in Example 1 and Comparative Example 1 can be identified as diffraction peaks of the (111), (200) and (220) crystal planes of CoO (JCPDS 43-1004).
[0068] Figure 2 to Figure 6The corresponding SEM images are the flake ZIF-67 of product S1 in Example 1, the exfoliated ZIF-67 of product S2 in Example 1, the CoO@NC composite material prepared in Example 1, the CoO@NC composite material prepared in Comparative Example 1, and the accumulated ZIF-67 of product S2 in Comparative Example 2. Figure 2 It can be seen that the directly synthesized ZIF-67 has a flake structure and large particles. Figure 3 It can be seen that after the large ZIF-67 flakes were treated with NaBH4, the surface of the particles was no longer flat, and a wrinkled and peeled layered morphology appeared, but the particles were not obviously damaged. Figure 4 It can be seen that the CoO@NC composite material prepared in Example 1 is a porous block material formed by the accumulation of fine particles, and the particle size is 10nm to 50nm. Figure 5 It can be seen that the morphology of the CoO@NC composite material prepared in Comparative Example 1 is similar to that of the CoO@NC composite material prepared in Example 1, and both are formed by the accumulation of small balls, and the size of the small balls is about 15nm to 100nm. It can be seen that the flat sheet structure is prone to structural collapse during high-temperature carbonization, resulting in particle clusters, while the wrinkled sheet-like accumulated material has a certain mutual support between the sheets, and is not easy to collapse completely at a higher temperature, so the derived particles are more dispersed. Figure 6 It can be seen that only by slowly adding NaBH4 aqueous solution to the ZIF-67 suspension for ultrasonic treatment, the rhombic flaky particle morphology of ZIF-67 is destroyed, and small-sized flakes are piled up, and the flake surface does not have a wrinkled flake morphology, so the same effect as Example 1 is not achieved. Such piled-up flake materials are prone to structural collapse during calcination, which is not conducive to the construction of a highly dispersed structure of nanoparticles.
[0069] Figure 7-8 The TEM images of the CoO@NC composite material prepared in Example 1 and the CoO@NC composite material prepared in Comparative Example 1 respectively. Figure 7 It can be seen that the CoO@NC composite material prepared in Example 1 is formed by the accumulation of extremely small particles, and the particle size is small and relatively dispersed. Figure 8 It can be seen that the CoO@NC composite material prepared in Comparative Example 1 is formed by the accumulation of small particles, the particle size is uneven, and there is a certain amount of agglomeration. The highly dispersed nanoparticles have highly dispersed active sites, which can increase the contact between the active sites and the substrate, which is beneficial to the catalytic performance of the material and improves the utilization rate of active atoms.
[0070] Fig. 9 The N2 adsorption-desorption curves of the flake ZIF-67 of the product S1 in Example 1 and the exfoliated ZIF-67 of the product S2 in Example 1 at 77K are shown. Fig. 9It can be seen that the N2 adsorption / desorption isotherms of flake ZIF-67 and exfoliated ZIF-67 at 77 K show the characteristics of typical type II adsorption / desorption curves. Among them, the BET specific surface area of flake ZIF-67 is only 5.01 m 2 / g, and its BJH pore volume is 0.013m 3 / g; the specific surface area of exfoliated ZIF-67 is 394.92m 2 / g, and its BJH pore volume is 0.076m 3 / g. Compared with the untreated sample, the specific surface area of ZIF-67 after NaBH4 stripping is greatly increased, and the increased pores are mostly micropores, which is conducive to the maintenance of the pores during the calcination process. Therefore, the ZIF material treated with this method is a very ideal precursor material.
[0071] Fig.10 The N2 adsorption-desorption curves of the CoO@NC composite material prepared in Example 1 and the CoO@NC composite material prepared in Comparative Example 1 at 77K are shown in FIG. Fig.10 It can be seen that the N2 adsorption / desorption isotherms of the CoO@NC composite material prepared in Example 1 and the CoO@NC composite material prepared in Comparative Example 1 at 77K show the characteristics of a typical type II adsorption / desorption curve, wherein the BET specific surface area of the CoO@NC composite material prepared in Example 1 is 128.66 m 2 / g, and its BJH pore volume is 0.146m 3 / g; the specific surface area of the CoO@NC composite material prepared in Comparative Example 1 is 22.69m 2 / g, and its BJH pore volume is 0.062m 3 / g. It can be seen that the CoP@C material prepared by exfoliating ZIF-67 has a large specific surface area and pore volume, and the rich pore structure provides a guarantee for the enrichment of degradation substrates in the confined space of the material and the material transport during the catalytic process. Therefore, the CoO@NC composite material prepared in Example 1 is a very ideal catalyst material.
[0072] Fig.11 The pore size distribution diagram of the CoO@NC composite material prepared in Example 1 and the CoO@NC composite material prepared in Comparative Example 1. Fig.11 It can be seen that the pore size distribution of the CoO@NC composite material prepared in Example 1 is about 1.6nm to 20nm, with a strong peak at 1.74nm. In comparison, the pore peak intensity of the CoO@NC composite material prepared in Comparative Example 1 is very weak, indicating that the material has fewer pores. The rich pore characteristics of the CoO@NC composite material prepared in Example 1 are of great significance to the material transport performance of the material.
[0073] Test Example 2
[0074] The catalytic performance test of the material is as follows: a 20 ppm ofloxacin aqueous solution is prepared, to which a ground catalyst solid is added, the concentration of which is 100 mg / L, the suspension is ultrasonicated for 10 minutes and shaken on a shaker for 20 minutes to achieve the ofloxacin adsorption-desorption equilibrium of the solid catalyst, and then the oxidant potassium permonosulfate (0.66 ppm) is added and continued to shake, and the reaction is carried out for 1 minute, 3 minutes, 5 minutes, 7 minutes and 10 minutes respectively, 2 mL of the reaction solution is drawn with an injection, the solid is quickly filtered using a 0.45 μm PTFE membrane and injected into 1 mL of methanol to quench the free radicals therein, and then the concentration of ofloxacin in each solution is monitored by UV-visible spectroscopy, and its concentration is confirmed based on the peak intensity at 288 nm combined with the standard curve.
[0075] When the adsorption-desorption equilibrium is reached after stirring for 30 minutes, the CoO@NC composite material prepared in Example 1 adsorbs 29.8% of ofloxacin. When potassium persulfate is added, the removal efficiency of ofloxacin is 78% after only 1 minute of ultrasound. After ten minutes of reaction, the total removal efficiency is 92.9%, and the concentration of Co ions dissolved in the solution after the reaction is as low as 0.10ppm. It can be seen that the MOF material prepared by this method has fast and efficient catalytic performance and high stability. The CoO@NC composite material prepared in Example 2 adsorbs 25% of ofloxacin. After ten minutes of reaction, the total removal efficiency of ofloxacin is 92.1%, and the concentration of Co ions dissolved in the solution after the reaction is as low as 0.12ppm. The material also has high catalytic activity and stability. After 30 minutes of treatment, the CoO@NC composite material prepared in Example 3 has an adsorption capacity of 31% of ofloxacin. After ten minutes of reaction, the total removal efficiency of ofloxacin is 93.1%, and the concentration of Co ions dissolved in the solution after the reaction is as low as 0.08ppm. The material also has high catalytic activity and stability. The CoO@NC composite material prepared in Comparative Example 1 adsorbed 21% of ofloxacin. After ten minutes of reaction, the total removal efficiency of ofloxacin was 88.5%, and the concentration of dissolved Co ions in the solution after the reaction was as low as 0.11 ppm. Compared with the example, the catalytic speed and total removal efficiency of the material were reduced.
[0076] In addition, the degradation effect of ofloxacin antibiotic by the CoO@NC composite material prepared in Example 1 and the CoO@NC composite material prepared in Comparative Example 1 is shown in the figure below: Fig.12 As shown. Fig.12It can be seen that when only potassium persulfate is added without any catalyst, ofloxacin is basically not degraded, and the concentration is reduced by only 4.5%; the CoO@NC composite material prepared in Example 1 has the best catalytic effect. When stirring for 30 minutes to reach adsorption-desorption equilibrium, Example 1 adsorbs about 29.8% of ofloxacin. When potassium persulfate is added, after ten minutes of reaction, its total removal efficiency is 92.9%, and the concentration of Co ions dissolved in the solution after the reaction is 0.10ppm. The absorption efficiency of the CoO@NC composite material prepared in Comparative Example 1 is 21%, and its total removal efficiency is 88.5%, and the concentration of Co ions dissolved in the solution after the reaction is 0.11ppm. Compared with Comparative Example 1, the CoO@NC composite material prepared in Example 1 degrades faster, and 78% of ofloxacin can be removed in just one minute.
[0077] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a CoO@NC composite material, characterized in that: The following steps are involved: S1: adding NaBH4 solid to the sheet ZIF-67 under ultrasonic conditions, and continuing the ultrasonic reaction to obtain the exfoliated ZIF-67; the exfoliated ZIF-67 has wrinkles on its surface; S2: calcining the exfoliated ZIF-67 under an inert atmosphere to obtain the CoO@NC composite material; In S1, the mass ratio of the flaky ZIF-67 to the NaBH4 solid is 1:(0.2~0.6).
2. The method for preparing the CoO@NC composite material according to claim 1, characterized in that: In S1, the ultrasonic reaction time is 2h~10h.
3. The method for preparing the CoO@NC composite material according to claim 1, characterized in that: In S2, the calcination temperature is 400°C to 650°C, and the calcination time is 2h to 10h.
4. The method for preparing the CoO@NC composite material according to claim 1, characterized in that: In S2, the heating rate of the calcination is 0.5°C / min to 2°C / min.
5. The method for preparing the CoO@NC composite material according to claim 1, characterized in that: In S1, the preparation method of the flaky ZIF-67 comprises the following steps: adding 2-methylimidazole solution to Co(NO3)2·6H2O solution with stirring, and continuing to stir the reaction to obtain flaky ZIF-67.
6. The method for preparing the CoO@NC composite material according to claim 5, characterized in that: The concentration ratio of the Co(NO3)2·6H2O solution to the 2-methylimidazole solution is 1:(1-4).
7. A CoO@NC composite material obtained by the preparation method of the CoO@NC composite material according to any one of claims 1 to 6.
8. The CoO@NC composite material according to claim 7, characterized in that: The CoO@NC composite material is a porous block material with a particle size of 10nm-50nm.
9. Use of the CoO@NC composite material as claimed in claim 7 or 8 in catalytic degradation of antibiotics.
